2017
DOI: 10.1371/journal.pgen.1007114
|View full text |Cite
|
Sign up to set email alerts
|

ciRS-7 exonic sequence is embedded in a long non-coding RNA locus

Abstract: ciRS-7 is an intensely studied, highly expressed and conserved circRNA. Essentially nothing is known about its biogenesis, including the location of its promoter. A prevailing assumption has been that ciRS-7 is an exceptional circRNA because it is transcribed from a locus lacking any mature linear RNA transcripts of the same sense. To study the biogenesis of ciRS-7, we developed an algorithm to define its promoter and predicted that the human ciRS-7 promoter coincides with that of the long non-coding RNA, LINC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 31 publications
11
74
0
Order By: Relevance
“…Recently, the genomic structure around the ciRS-7 precursor has been independently reported (Barrett et al, 2017). In agreement with our analysis, this study showed that the promoter region of ciRS-7 overlaps an upstream long non-coding transcript (LINC00632 locus), suggesting that the ciRS-7 precursor is a long non-coding RNA (Barrett et al, 2017).…”
Section: Previous Results Are Consistent With the Mir-dependent Back-supporting
confidence: 90%
See 1 more Smart Citation
“…Recently, the genomic structure around the ciRS-7 precursor has been independently reported (Barrett et al, 2017). In agreement with our analysis, this study showed that the promoter region of ciRS-7 overlaps an upstream long non-coding transcript (LINC00632 locus), suggesting that the ciRS-7 precursor is a long non-coding RNA (Barrett et al, 2017).…”
Section: Previous Results Are Consistent With the Mir-dependent Back-supporting
confidence: 90%
“…Recently, the genomic structure around the ciRS-7 precursor has been independently reported (Barrett et al, 2017). In agreement with our analysis, this study showed that the promoter region of ciRS-7 overlaps an upstream long non-coding transcript (LINC00632 locus), suggesting that the ciRS-7 precursor is a long non-coding RNA (Barrett et al, 2017). The BAC clones obtained (185 and 200 kb) cover from the promoter of this non-coding transcript (LINC00632) to far downstream of the ciRS-7 exon and they were found to produce mature ciRS-7.…”
Section: Previous Results Are Consistent With the Mir-dependent Back-mentioning
confidence: 99%
“…Our data also confirmed the existence of two human ciRS-7 isoforms measuring 1,485 and 1,301 bp ( Supplementary Fig. 2), caused by optional intron retention (Barrett, Parker, Horn, Mata, & Salzman, 2017;T B Hansen et al, 2011).…”
Section: Resultssupporting
confidence: 86%
“…Two studies investigated the role of CDR1as in vivo (Piwecka et al, 2017;Kleaveland et al, 2018). Although this circRNA is embedded in a long non-coding RNA locus (Barrett et al, 2017), the circularization of CDR1as is so efficient that previous studies could not detect any linear counterpart (Hansen et al, 2011(Hansen et al, , 2013Memczak et al, 2013). Also, Piwecka et al (2017) could not detect any RNAs generated from the opposite strand and concluded that CDR1as is the only gene directly affected by the deletion (Piwecka et al, 2017).…”
Section: Assessing the Function Of Circrnas In Vivomentioning
confidence: 99%